The Steam Educational Approach in the Pedagogical Practice of Early Childhood Teachers: Reality or Utopia? - Núñez, Raúl Prada; Tarazona, Mariana Elena Peñaloza; Moreno, Francisco Javier Rodríguez (Journal of Ecohumanism, 2025)
The STEAM educational approach with the passage of time has been contributing to the improvement of the effectiveness of the teaching process at different educational levels, since its interdisciplinary approach supported by the implementation of active methodologies such as project-based learning or gamification along with collaborative work, have allowed to ensure the active participation of students. Mixed research is carried out to report the competencies around this educational approach that exhibits a probabilistic sample of teachers linked to the official sector of a Colombian border city, who work in the Transition grade. The results show an incipient implementation process propitiated by the lack of teacher qualification around this educational approach, which demands public policies aligned with this approach that permeate school curricula together with their institutional pedagogical models and thus guarantee the development of the competencies demanded by today's society. Complementarily, the need to consider and work on the socioemotional competencies of both teachers and students was identified. It is expected that these results will contribute to the transformation of educational processes where the student is an active agent in his or her education, framed in relevant activities aimed at solving problems observed in everyday life.